Celastrol targets CKB-mediated futile creatine cycle in human brown adipocytes thermogenesis - Jingyi Ni; Baicheng Wang; Xinyue Liu; Rui Yin; Jinlin Tang; Siyu Hua; Xiaoxiao Zhang; Yangyang Wu; Shihu Zhang; Chenbo Ji (Metabolism Open)
Celastrol is widely recognized as one of the most potent anti-obesity agents, and its ability to promote adipocyte thermogenesis is thought to be a key mechanism. However, the precise molecular targets through which celastrol modulates thermogenesis in human adipocytes remain unclear. In this study, we synthesized a celastrol-based small molecular probe and employed a combination of photoaffinity labeling (PAL), click chemistry, and Surface Plasmon Resonance (SPR) to identify its direct binding targets. Our results reveal that celastrol directly interacts with creatine kinase B-type (CKB), leading to an increase in CKB protein stability. This suggests that celastrol modulates the futile creatine cycle within human brown adipocytes, thereby contributing to thermogenesis. Collectively, our findings provide new insights into the molecular mechanisms by which celastrol promotes thermogenesis in human brown adipocytes. Notably, we demonstrated that celastrol targets CKB-mediated futile creatine cycle for the first time. These findings not only deepen our understanding of celastrol's role in weight loss but also provides a potential strategy for obesity treatment.